Análise quantitativa dos resíduos de construção e demolição (RCD) na cidade de Pau dos Ferros-RN - Lima, Thayse Nunes de (Universidade Federal Rural do Semi-Árido, 2018)
Based on the analysis of the growth of civil construction in the municipality of Pau dos Ferros-RN and considering the remarkable increase of waste generated by these activities, this paper aims to identify the amount of construction and demolition waste generated by the works in together with its final provisions, since civil construction is directly linked to the socioeconomic development of the country and as a consequence, it is the largest contributor to the generation of RCDs. The execution of the methodological procedure was based on exploratory and descriptive elements followed by the use of a well-designed questionnaire to aid in the collection of the significant data applied to eight selected works in the municipality. According to the obtained answers, it was possible to observe how great is the generation of residues in construction and demolition, where these are responsible for innumerable impacts to the environment and compromising of the natural resources. In addition, it was found that a large part of the waste generated is disposed of in inappropriate places without supervision by both the responsible and the local residents, becoming a common action. Thus, the municipality of Pau dos Ferros is inefficient in the management of construction and civil demolition waste, where there is a need to implement more sustainable methods, such as in the state of Minas Gerais there are refuse recycling plants (Minas Gerais , 2006), to reduce the inappropriate disposal of these, in order to minimize environmental degradation and help in the socioeconomic and sustainable development of the municipality.
Keywords: Entulho; Rubble; Impacto ambiental; Environmental impact; Destinação final; Last destination; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA